2014
DOI: 10.1089/end.2014.0315
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nerve-Sparing Robot-Assisted Radical Cystoprostatectomy on Erectile Function in a Preoperatively Potent Population

Abstract: A cavernosal nerve-sparing robot-assisted approach to radical cystectomy allows for recovery of potency without sacrificing oncologic outcomes even with higher risk disease as compared to historical open or laparoscopic series. Further studies are required to help elucidate why some men have better recovery in this setting than others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Haberman et al and Asimakopoulos et al reported that 45% and 77.5% of patients, respectively, who received nerve-sparing RARC achieved potency. 17,18 Tyritzis et al showed that 74% and 88% of patients achieved daytime continence (1 pad per day) for 6 and 12 months, respectively, 19 whereas Asimakopoulos et al showed that 75% and 100% of patients experienced daytime continence (0 pad per day) for 1 and 12 months, respectively. 18 Recently, Kouk et al carried out single-port RARC with LND and intracorporeal ileal conduit in four patients with invasive bladder cancer.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Haberman et al and Asimakopoulos et al reported that 45% and 77.5% of patients, respectively, who received nerve-sparing RARC achieved potency. 17,18 Tyritzis et al showed that 74% and 88% of patients achieved daytime continence (1 pad per day) for 6 and 12 months, respectively, 19 whereas Asimakopoulos et al showed that 75% and 100% of patients experienced daytime continence (0 pad per day) for 1 and 12 months, respectively. 18 Recently, Kouk et al carried out single-port RARC with LND and intracorporeal ileal conduit in four patients with invasive bladder cancer.…”
Section: Surgical Techniquementioning
confidence: 99%
“…and Asimakopoulos et al . reported that 45% and 77.5% of patients, respectively, who received nerve‐sparing RARC achieved potency . Tyritzis et al .…”
Section: Introductionmentioning
confidence: 99%
“…As with radical prostatectomy, nerve sparing does help maintain sexual function. [102930] In a highly selected group, nerve sparing and seminal vesicle sparing may help preserve functional outcomes with over 70% reporting potency within 12 months of surgery; however, long-term oncological data are not available at this time, and this should be done with caution. [30] In addition, nerve sparing reports with short follow-up report oncologic outcomes are not compromised with this technique.…”
Section: Advances In Surgery For Muscle Invasive Bladder Cancermentioning
confidence: 99%
“…During RC, the lateral portion of each bladder vascular pedicle is stapled with a vascular staple load, and a second staple load is used to divide the proximal portion of the posterior pedicle. Clips and athermal dissection are used to divide the distal portion of the posterior pedicle, staying close to the seminal vesicles, thereby avoiding undue damage to the erectile nerves that are in close proximity lateral to the seminal vesicles [9] , [16] . In addition, a more extended PLND should be performed in RC compared with RP, and the erectile nerves are at risk of injury when the lymph nodes in the presacral and internal iliac area are being removed [17] .…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Nevertheless, the adoption of laparoscopic and robot-assisted technology has improved visualization and dexterity of pelvic surgeries. Several studies with varying results after nerve-sparing LRC have been published [8] , [9] , [10] . Herein we review the current available literatures concerning the anatomic basis, nerve-sparing techniques, and therapeutic effects of nerve-sparing LRC and RARC in male patients.…”
Section: Introductionmentioning
confidence: 99%